2013
DOI: 10.1371/journal.pone.0056138
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of an Uncommon Cellulosome-Related Protein Module from Ruminococcus flavefaciens That Resembles Papain-Like Cysteine Peptidases

Abstract: Background Ruminococcus flavefaciens is one of the predominant fiber-degrading bacteria found in the rumen of herbivores. Bioinformatic analysis of the recently sequenced genome indicated that this bacterium produces one of the most intricate cellulosome systems known to date. A distinct ORF, encoding for a multi-modular protein, RflaF_05439, was discovered during mining of the genome sequence. It is composed of two tandem modules of currently undefined function that share 45% identity and a C-terminal X-docke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…I1.2 is particularly intriguing, since biomass-modifying enzymes are directly involved in the deconstruction of lignocellulosic biomass. However, recent studies have suggested the presence of peptidases and proteases as members of Ruminococcus flavefaciens cellulossome, although the functional relevance of these enzymes is still not clear [27]. These observations are consistent with the detection of one Clostridium thermocellum serine protease and two serine proteases inhibitors (serpins), both containing one dockerin module [28,29].…”
Section: In Complexes C-[i] C-[ii] and C-[iii]supporting
confidence: 67%
“…I1.2 is particularly intriguing, since biomass-modifying enzymes are directly involved in the deconstruction of lignocellulosic biomass. However, recent studies have suggested the presence of peptidases and proteases as members of Ruminococcus flavefaciens cellulossome, although the functional relevance of these enzymes is still not clear [27]. These observations are consistent with the detection of one Clostridium thermocellum serine protease and two serine proteases inhibitors (serpins), both containing one dockerin module [28,29].…”
Section: In Complexes C-[i] C-[ii] and C-[iii]supporting
confidence: 67%
“…1 ). Sequence data and structural analysis have revealed that the dockerins of ScaB, CttA and a cysteine peptidase‐like scaffoldin [20] are different from the conventional symmetric dockerins, described earlier. They possess three insertions, one of which is positioned inside the second calcium‐binding loop [15].…”
Section: Introductionmentioning
confidence: 75%
“…Examples of frequent components include an N-terminal signal peptide, a MurNAc amidase, and one or multiple targeting domains, such as the LysM domain, the peptydoglycan binding domain (PGBD), the choline binding domain (CGD), and the bacterial SH3b domain34. Recently, the crystal structure of a CHAP domain has been characterized as a cellulosome-related module, indicating that this family of cysteine peptidases might modulate processes other than cell-wall hydrolysis46. CHAP domains have been unified under the peptidase families C40 and C51 in the MEROPS database23, under Pfam47 domains NlpC/P60 (PF00877) and CHAP (PF05257), and under the COG database48 entries COG0791 ‘cell-wall-associated hydrolases (invasion-associated proteins)’ and COG3942 ‘surface antigen’.…”
Section: Resultsmentioning
confidence: 99%
“…CHAP superfamily members also share structural similarities that cannot be detected at the sequence level46. Beyond the catalytic core, the structures are highly divergent through deletions and insertions of structural elements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation